2020
DOI: 10.1016/j.ijid.2020.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemia as a sensitive biomarker of disease severity and the requirement for invasive mechanical ventilation requirement in COVID-19 pneumonia: A case series of 306 Mediterranean patients

Abstract: Highlights There is a high prevalence of hypokalemia among patients with COVID-19 pneumonia. This suggests the presence of a disorder in the renin-angiotensin system activity. Hypokalemia is associated with requiring invasive mechanical ventilation. Hypokalemia seems to be a sensitive biomarker of severity-progression of COVID-19. Serum levels of potassium should be closely monitored in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 18 publications
4
62
5
Order By: Relevance
“…Thus, our multicenter study confirmed that hyponatremia is frequent in COVID-19 adults, found in 20.4% of the patients. In our study, we did not find significant association between COVID-19 severity and hypokalemia (p = 0.056), contrary to the previous study [ 12 ]. Moreno-P et al found that hypokalemia (potassium ≤ 3.5 mmol/l) was independently associated with requiring invasive mechanical ventilation (odds ratio: 8.98, 95% CI 2.54–31.74).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, our multicenter study confirmed that hyponatremia is frequent in COVID-19 adults, found in 20.4% of the patients. In our study, we did not find significant association between COVID-19 severity and hypokalemia (p = 0.056), contrary to the previous study [ 12 ]. Moreno-P et al found that hypokalemia (potassium ≤ 3.5 mmol/l) was independently associated with requiring invasive mechanical ventilation (odds ratio: 8.98, 95% CI 2.54–31.74).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreno-P et al described 306 COVID-19 patients in Spain with potassium measured in the first 72 h of admission. They found that hypokalemia was independently associated with requiring invasive mechanical ventilation, but mortality was not influenced by low potassium [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is compelling evidences that patients with acute kidney injury at admission exhibit activation of RAAS, as documented by higher plasmatic renin and aldosterone levels and lower urinary sodium levels in patients with acute kidney injury [ 109 ], as well as the association of plasmatic aldosterone and C-reactive protein levels and COVID-19 severity [ 110 ]. Since hypokalaemia was found to be prevalent in patients with COVID-19 pneumonia (~ 30%) and is an indicator of RAAS activity, it was suggested that hypokalaemia could be used as a surrogate marker of COVID-19 progression and an independent risk factor for invasive mechanical ventilation requirement [ 111 ]. Conversely, mean serum concentrations of ACE2, Ang II, and aldosterone, as well as potassium levels and blood pressure, were found to be similar in patients with COVID-19 and the control group [ 112 ].…”
Section: Comorbidities and Ace/ace2 Balance Disruptionmentioning
confidence: 99%
“…hypokalemia has been noticed in the literature before as one of the complications among patients, in a cohort Chinese study that had a total of 175 patients 95 (55%) patients had hypokalemia, 31 (18%) had sever hypokalemia of less than 3 (mmol/L) and 64 (37%) patients had hypokalemia ranges between 3 and 3.5 (mmol/L). [ 16 ] Degree of hypokalemia found to be in direct correlation with disease severity, and an independent early marker of disease progression [ 17 ].Patients with severe or critical COVID-19 who survive may have a long road to recovery while experiencing the lasting effects of the infection and treatments [ 18 ]. Some of COVID-19 patients need long term follow up to observe and manage any new or established complication specifically if this complication has a potential life-threatening effect as in our case with hypokalemia and the sequela of its management.…”
Section: Discussionmentioning
confidence: 99%
“…When SARS-CoV-2 binds and degrades ACE2, the ability of ACE2 to regulate RAS is reduced and it cannot antagonize ACEI-2. The final result is RAS activity is increased, which acts like secondary increased aldosterone [ 17 ]. Increased RAS activity enhances the distal delivery of sodium and water to collecting tubule of the kidney and the excretion of potassium, because previous literature also has shown that serum K+ is negatively associated with plasma renin activity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%